2010
DOI: 10.1523/jneurosci.2570-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylglucosamine 6-O-Sulfotransferase-1-Deficient Mice Show Better Functional Recovery after Spinal Cord Injury

Abstract: Neurons in the adult CNS do not spontaneously regenerate after injuries. The glycosaminoglycan keratan sulfate is induced after spinal cord injury, but its biological significance is not well understood. Here we investigated the role of keratan sulfate in functional recovery after spinal cord injury, using mice deficient in N-acetylglucosamine 6-O-sulfotransferase-1 that lack 5D4-reactive keratan sulfate in the CNS. We made contusion injuries at the 10th thoracic level. Expressions of N-acetylglucosamine 6-O-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 48 publications
3
57
0
Order By: Relevance
“…5A). The proteoglycan-mediated inhibition of neurite growth was blocked by K-II and C-ABC, and the effects of K-II and C-ABC were comparable to each other, and also consistent with our previous study (Ito et al, 2010). To our surprise, the combination of K-II and C-ABC showed neither synergistic nor additive effects (Fig.…”
Section: Restoration Of Neurite Outgrowth By K-iisupporting
confidence: 92%
See 3 more Smart Citations
“…5A). The proteoglycan-mediated inhibition of neurite growth was blocked by K-II and C-ABC, and the effects of K-II and C-ABC were comparable to each other, and also consistent with our previous study (Ito et al, 2010). To our surprise, the combination of K-II and C-ABC showed neither synergistic nor additive effects (Fig.…”
Section: Restoration Of Neurite Outgrowth By K-iisupporting
confidence: 92%
“…The granular staining profile in Figure 1 D represented the main source of KS expression, i.e., microglia ( Fig. 1 E), which is consistent with previous reports (Jones and Tuszynski, 2002;Ito et al, 2010). As disulfated KS was still detected after K-II treatment by disaccharide analysis using HPLC (Fig.…”
Section: In Vitro and In Vivo Degradation Of Ks By K-iisupporting
confidence: 89%
See 2 more Smart Citations
“…The thinly myelinated axons in the shi-NS/PC group could not conduct signals very well, resulting in an increased MEP latency and a smaller amplitude in the shi-NS/PC group compared with the wt-NS/PC group. Recent studies have established MEP as a sensitive technique for recording conduction in the CNS [14,36,[68][69][70]. Eftekharpour et al [56] demonstrated a significantly shortened latency in the spinal cord-evoked potential in adult shiverer mice after wild-type NS/PCs transplantation, suggesting that conduction differences could be owing to spinal cord myelination, all else being equal.…”
Section: Discussionmentioning
confidence: 99%